2018
DOI: 10.1124/mol.118.112615
|View full text |Cite
|
Sign up to set email alerts
|

An Outward-Facing Aromatic Amino Acid Is Crucial for Signaling between the Membrane-Spanning and Nucleotide-Binding Domains of Multidrug Resistance Protein 1 (MRP1; ABCC1)

Abstract: The 190-kDa human MRP1 is an ATP-binding cassette multidrug and multiorganic anion efflux transporter. The 17 transmembrane helices of its three membrane-spanning domains, together with its two nucleotide binding domains (NBDs), form a stabilizing network of domain-domain interactions that ensure substrate binding in the cytoplasm is efficiently coupled to ATP binding and hydrolysis to effect solute efflux into the extracellular milieu. Here we show that Ala substitution of Phe in an outward-facing loop betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…In summary, our results support the notion that ATP hydrolysis is required to drive the transport cycle at the resetting step from the OF to the IF state. We anticipate that our results provide a mechanistic framework to understand the functional role of the extracellular gate of type I ABC exporters and to explain the molecular underpinning of disease-causing mutations found in the extracellular region of medically important ABC exporters as recently investigated for MRP1 and CFTR 32,33 .…”
Section: Discussionmentioning
confidence: 84%
“…In summary, our results support the notion that ATP hydrolysis is required to drive the transport cycle at the resetting step from the OF to the IF state. We anticipate that our results provide a mechanistic framework to understand the functional role of the extracellular gate of type I ABC exporters and to explain the molecular underpinning of disease-causing mutations found in the extracellular region of medically important ABC exporters as recently investigated for MRP1 and CFTR 32,33 .…”
Section: Discussionmentioning
confidence: 84%
“…bMrp1 cryo-EM structures to complement previous models based on the bacterial nucleotide-bound homodimeric Sav1866 from Staphylococcus aureus and substrate-free heterodimeric TM287 and TM288 from Thermotoga maritima crystal structures (48,49). The models indicated that replacing the bulky Met 1093 in hMRP1 with a nonconservative, cavity-creating Ala might disrupt the proposed hydrophobic H-pocket around the arachidonic acid moiety of LTC 4 (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…We hope that our results provide a mechanistic framework to further study the functional role of the extracellular gate of type I ABC exporters and to investigate the molecular underpinning of disease-causing mutations found in the extracellular region of medically important ABC exporters such as MRP1 and CFTR 34,35 .…”
Section: Discussionmentioning
confidence: 93%